2017
DOI: 10.4081/mr.2017.7295
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibiotic resistance and blaIMP-1 gene among Pseudomonas aeruginosa strains isolated from burn and urinary tract infections in Isfahan, central Iran

Abstract: Pseudomonas aeruginosa is one of the most important opportunistic pathogens responsible for various types of hospital infections. High prevalence of antibiotic resistance in P. aeruginosa strains of human clinical samples cause more severe diseases for a longer period of time. The current research was done in order to study the distribution of blaIMP-1 gene among the imipenem-resistant P. aeruginosa strains isolated from burn and urinary tract infections of hospitalized patients. Two-hundred and forty-three P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…In another study, the statistical analysis results showed that the incidence rate of MDR/XDR in uropathogenic bacteria (including P. aeruginos), obtained from inpatients was significantly higher than in those obtained from out-patients [30] . In a study by Hashemi et al (2017), resistance to most antibiotics was higher in P. aeruginosa isolates isolated from hospitalized patients compared to those isolated from out-patients [31] . In addition, Farajzadeh Sheikh et al (2020) found that the prev-alence of MDR P. aeruginosa isolates was higher among patients admitted to the burn ward compared to other wards [32] .…”
Section: Discussionmentioning
confidence: 93%
“…In another study, the statistical analysis results showed that the incidence rate of MDR/XDR in uropathogenic bacteria (including P. aeruginos), obtained from inpatients was significantly higher than in those obtained from out-patients [30] . In a study by Hashemi et al (2017), resistance to most antibiotics was higher in P. aeruginosa isolates isolated from hospitalized patients compared to those isolated from out-patients [31] . In addition, Farajzadeh Sheikh et al (2020) found that the prev-alence of MDR P. aeruginosa isolates was higher among patients admitted to the burn ward compared to other wards [32] .…”
Section: Discussionmentioning
confidence: 93%
“…Bacteria also have a greenish-yellow pyoverdin pigment, and these pigments are dissolved in water [12,13] in addition to having a layer of alginate and a biofilm, which increases its resistance to antibiotics [14] Resistance of P. aeruginosa to antibiotics and disinfectants is a major problem all over the world due to the random and unrestricted use of antibiotics [15]. This resistance is also likely to occur due to several reasons, including the production of beta-lactamase enzymes and the lack of permeability of their cell wall, as well as the possibility of it containing and acquiring resistance genes from another bacterial genus by plasmids and transposons via bacterial conjugation and the occurrence of genetic mutations in the genes leading to the development of resistance to these antiseptics and causing failure in treating infections caused by P.aeruginosa bacteria [16,17].…”
Section: Journal Of Applied Sciences and Nanotechnologymentioning
confidence: 99%